Study on the nonlinear response and shear behavior of RC columns under lateral impact. (December 2021) - Zhou, Xiwu; Zhou, Ming; Luo, Dongmei; Wu, Benying; Liu, Lingfei
Abstract: In the present study, in view of the problem of nonlinear response caused by vehicle-RC pier collision, a new test system which can realize lateral impact is proposed, and two types of 1:3 scale RC components in five groups are subject to the lateral impact test at a velocity of 4.5 m/s. The system's design characteristics represent the effect of stirrup spacing and axial compression ratio on the dynamic response of RC columns. In addition, the nonlinear response results of RC columns, such as impact force, acceleration, lateral displacement, failure mode and degree, are given in the test. Digital Image Correlation (DIC) technology is applied to the test. Next, the lateral strain response of RC columns during impact is measured, and the strain change process in every representative region is calculated. The data outlined in this study provide a reasonable basis for evaluating the shear capacity of RC columns and developing a finite element model (FEM). Finally, a typical FEM of vehicle-pier collision scenario is developed, while an improved equation for calculating the axial compression ratio-shear increment and a simplified calculation value of dynamic shear capacity of the RC pier are proposed.